Use of Etonogestrel implant beyond approved duration - A case report - Carvalho,Carolina Castro (2022)
Abstract The contraceptive implant is the most effective method of reversible contraception. Observational and trial data indicate that this method remains effective beyond the initially approved duration of use. We report a case of etonogestrel serum levels above the supposed threshold value for ovulation suppression nine years after implant insertion.